Underlying Differences in the Treatment of Left Ventricular Thrombus With Non-Vitamin K Antagonist Oral Anticoagulants - Leow, Aloysius Sheng-Ting (EXCERPTA MEDICA INC-ELSEVIER SCIENCE INC, 2021)
10.1016/j.amjcard.2019.07.001